The use of Libras as a means of facilitating nursing care for deaf patients - Pissolato, Bruna Lucas; Moreira, Yohana; Monteiro, Ana Claudia Moreira (Seven Editora, 2023)
The current article identifies the struggle of the deaf community facing the difficulty in nursing care, such as strategy that nurses and others healthcare professionals use to assist the deaf community, considering the unpreparation from the staff. The objective is to bring up the importance of Brazilian Sign Language (LIBRAS) use to healthcare professionals in order to exist a reliable communication between deaf people and those professionals. It is narrative bibliographic research with a qualitative descriptive and exploratory approach. The research was based in BDENF, LILACS and SciELO databases through the following keywords: deaf, nursing and LIBRAS. Six (6) articles were found within the above keywords. One (1) was excluded for not addressing the subject in question. Five (5) articles were available in full according to the inclusion and exclusion criteria. It is necessary to indicate the importance of knowing Brazilian Sign Language from healthcare professionals, even in a basic way to offer a proper caring to deaf community. DOI:https://doi.org/10.56238/sevened2023.004-038